CDK inhibitors-induced SSAT expression requires NF kappa B and PPAR gamma in MCF-7 breast cancer cells - Yıldırım, Şeyma; Öztürk, Mert Burak; Berrak, Özge; Çoker Gürkan, Ajda; Ünsal Palavan, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (TUBİTAK Scientific & Technical Research Council Turkey, Ataturk Bulvarı No 221, Kavaklıdere, Ankara, 00000, Turkey, 2015)
The cyclin-dependent kinase (CDK) inhibitors purvalanol and roscovitine are therapeutic agents that control cell proliferation through regulating cell-cycle machinery. They also affect polyamine (PA) metabolism, which is activated in malignant tissues. Therefore, PA catabolism became a remarkable target in cancer therapies. Induction of the PA catabolic enzyme spermidine/spermine N-1-acetyltransferase (SSAT) is under the control of transcription factors such as NF kappa B and PPAR gamma. The purpose of this study was to investigate the therapeutic potential of CDK inhibitors in combination with PAs in MCF-7 breast cancer cells. In order to understand the involvement of PA catabolic enzyme SSAT in this process we also checked its transcriptional regulation in the presence of CDK inhibitors. MCF-7 cells were exposed to CDK inhibitors in the absence or presence of Spd and Spm. Cell viability loss was evaluated by MTT assay. Apoptosis was determined by annexin-V/PI staining using FACS flow. The SSAT transcription level was measured by qRT-PCR. Intracellular PA pool was determined by HPLC. Protein expressions were assessed by western blotting. We found that CDK inhibitors decreased cell viability in a time-dependent manner and induced apoptosis. Co-treatment of Spd or Spm with CDK inhibitors prevented the apoptotic potential of both drugs. Purvalanol increased SSAT expression levels in a time-dependent manner. Although the induction of SSAT by purvalanol resulted in the activation of NF kappa B at early time points, induction was accomplished by PPAR gamma as a late response after purvalanol treatment. We concluded that both transcriptional control mechanisms could be responsible for SSAT regulation in a time-dependent manner.
Keywords: Polyamines; SSAT; Purvalanol; PPAR gamma; NF kappa B; Spermidine/Spermine N-1-Acetyltransferase SSAT; Induced Apoptosis; Colon-Cancer; Polyamine Metabolism; Carcinoma Cells; Activation; Induction; Roscovitine; Autophagy; Alpha